Erasmus and Christian Humanist Latin. Issue 2 (3rd July 2017) - MacPhail, Eric
Abstract : This essay looks at the quarrel of Ciceronianism among European Renaissance humanists from the perspective of Erasmus's biblical scholarship and his evangelical understanding of the proper relationship between the mind and the speech of a Christian. These issues emerge from a contextual reading of his Dialogus Ciceronianus of 1528 that relies not only on the history of Renaissance debates over imitation but also and primarily on Erasmus's understanding of human and divine logos as developed in his Lingua and particularly in the Paraphrases on the New Testament . Our reading will focus on some key metaphors that circulate among these Erasmian texts including the metaphor of the mirror and its implications for Christian identity.